Loan-use System of Gourami Breeders (Osphronemus gouramy) at Seeding Gourami Business in Nagari Mungo Luak Subsdistrict Lima Puluh Kota District West Sumatera Province - Indah Novelia; Hamdi Hamid; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in january – february 2017 which located in Nagari Mungo Luak subsdistrict Lima Puluh Kota district West Sumatera province. This study aims to to analyze loan-use Gourami breeders (Osphronemus gouramy) based on kinship systems and sharing results system loan-use gourami breeders at seeding fish business the community Nagari Mungo. Methods used in this research is a method survey with the number of respondents from 15 people, where the determination of respondents were with purposive sampling. Loan-use system breeders fish were 2 categories lending breeders based on kinship an ancestor or because between one residence and lending based on kinship according to offspring or kinship ties. Loan-use category 1 the size of the ratio of the agreed by 50:50 it means share of the profits balanced that is 50 if the management and 50 for the owners , while system and loan use category 2 the size of the ratio of the in agreed of 60:40 it means management could get a share more namely 60 and the owner of is only 40 a share of the profits income .Keywords: loan-use system, sharing results, seeding, gourami